APOPTOSIS INDEX BETWEEN FEMALES AND MALES IN REGULAR HEMODIALYSIS - Djoko Santoso (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
Many reports have documented apoptosis index in hemodialysis patients, but to date, no single study has directly compared the apoptosis index of males to females. Data on mortality rate among hemodialytic patients in the hemodialysis center at the Department of Internal Medicine Dr Soetomo General Hospital, Surabaya, Indonesia show a high number predominated by female patients. Therefore, to answer the question of whether there is a gender difference in apoptosis index, the researcher studied leukocyte responses in male and female hemodialysis patients. The apoptosis index of the sample was measured by indirect immunoassay method. Cell lyses, followed by immunochemical determination of histone-complexed DNA fragments in a microtiter plate wells. The apoptosis quantization was obtained by determining the amount of colored product spectrophotometrically. One hundred and four non-diabetic subjects who received hemodialysis (HD), and 24 normal controls (NC), were evaluated. The apoptosis index in ESRD patients group and control group showed no significant difference (0.6172 vs 0.4008, p=0.114), neither did it vary in both sexes and age groups. When the sex factor was analyzed (after exclusion from the diabetic ESRD patients), females apoptosis index was significantly higher than that of the males (0.7325 vs 0.55175, p<0.05). In conclusion, apoptosis index in females among non-diabetic patients undergoing hemodialysis is higher than that occur in males and controls.